Hospitalizations and cardiac sarcoidosis: insights into presentation and diagnosis from the nationwide readmission database - Abraham, Jacob; Spinelli, Kateri; Li, Hsin-Fang; Pham, Tuan; Wang, Mansen; Sheikh, Farooq H. (Frontiers in Cardiovascular Medicine, 2024)
IntroductionCardiac sarcoidosis (CS) is an increasingly recognized cause of cardiac disease. Because the clinical presentation of CS is non-specific, the diagnosis is often delayed. Early detection is essential to initiate treatments that reduce the risk of heart failure (HF) and arrhythmic death. We therefore aimed to describe the features of CS hospitalizations during which the initial diagnosis of CS is made.MethodsWe performed a retrospective analysis of hospitalizations from 2016 to 2019 in the Nationwide Readmission Database (NRD). Hospitalizations with a primary diagnosis suggestive of CS (HF/cardiomyopathy, cardiac arrest, arrhythmias, or heart block) were categorized into cases with and without CS as a secondary diagnosis (CS+ and CS−, respectively). One-to-one propensity score matching (PSM) was performed.ResultsThe CS+ cohort comprised 1,146 hospitalizations and the CS− cohort 3,250,696 hospitalizations. The CS+ cohort included patients who were younger and more often male. PSM resulted in highly matched cohorts (absolute standardized mean difference <0.1). Primary diagnoses of ventricular arrhythmias (VA) or heart block were more frequent in matched CS+ hospitalizations, whereas primary diagnosis of HF/cardiomyopathy was more frequent in matched CS− hospitalizations. The matched CS+ group exhibited higher rates of in-hospital procedures and longer length of stay. In-hospital mortality and 30-day readmission were similar between matched cohorts.DiscussionThese findings highlight increased rates of CS in younger males with primary diagnoses of VA and heart block, and increased use of diagnostic and therapeutic interventions such as pacemaker and left ventricular assist device implantation, and could aid clinicians in more timely diagnosis and treatment of CS.